Defenders of the status quo: making sense of the international discourse on transfer pricing methodologies. Issue 1 (2nd January 2022) - Brugger, Fritz; Engebretsen, Rebecca
Abstract: Over a third of international trade happens within, rather than between, corporations. This makes establishing transfer prices – the price of transactions within and between related corporations – pivotal, as it defines corporations' tax bills. Tax authorities worldwide follow the OECD transfer pricing guidelines and its accompanying methods for taxing corporations. This despite the guidelines' well-documented weaknesses and even though alternative and potentially simpler methods exist. Existing literature helps explain why the OECD guidelines continue to dominate but not how those in favor of the status quo will go about defending them. We offer a novel, theory-based framework, to explain how supporters of the status quo – the epistemic community – will respond, using a combination of strategies targeting the policy discourse but also policy makers, in an effort to bolster the legitimacy of the OECD guidelines. We use discourse network analysis to study the debate on simplified transfer pricing methods from 1995 to 2018 and the positions of actors engaged. Our data confirms that the epistemic community deploys a hypothesized mix of strategies to ensure the durability of the OECD guidelines and accompanying methods, at the same time undermining the position of alternative approaches.